Molecular Genetics of Bacteria - Dale, Jeremy W Park, Simon (John Wiley & Sons, 2004)
Presenting the basic concepts and most exciting developments, this textbook provides an introduction to the molecular genetics of bacteria in a form suitable for the needs of students studying microbiology, biotechnology, molecular biology, biochemistry, genetics and related biomedical sciences.